Structural Condition Assessment of Reinforced Concrete Bridge Using Operational Modal Analysis and Finite Element Model - Muhammad, Hussein; Abdul Kudus, Sakhiah; Jamadin, Adiza; Saidin, Siti Shahirah (International Journal of Sustainable Construction Engineering and Technology, 2024)
The integration of Operational Modal Analysis (OMA) and Finite Element Model (FEM) techniques has proven to be a valuable approach for evaluating and maintaining the health of such structures. OMA extracts dynamic characteristics from a bridge’s responses to ambient vibrations, while FEM employs computational models to simulate and compare these dynamic behaviours. This comprehensive methodology ensures an accurate representation of the bridge’s behaviour and its correlation with real-world conditions. However, a significant challenge arises in assessing the Ultra High Performance Fiber Reinforced Concrete (UHPFRC) pedestrian bridge in Klang, Selangor, launched in October 2022, due to limited available information about OMA and FEM on UHPFRC. This research aims to develop FEM and conduct ambient vibration tests to obtain modal parameters. Moreover, the study investigates OMA techniques in the context of weak excitation sources, filling a critical knowledge gap. By comparing experimental results with FEM, this research provides insights into the feasibility and reliability of OMA under challenging environmental conditions. The principal results reveal significant percentage differences in natural frequencies between FEM and OMA, with the most notable disparities occurring in the first mode. Nevertheless, the mode shapes extracted from OMA closely resemble those from FEM. In conclusion, this research enhances the understanding of UHPFRC pedestrian bridge behaviour and modal analysis techniques.